Determinants That Influence the Implementation of Generic Open Source Management Information System Version 2 (SIMGOSV2) at Ryacudu Regional General Hospital Kotabumi Lampung - Ayu Lestari Nofiyanti; Kosasih Kosasih; Rahadian Malik; Vip Paramarta; Taufan Nugroho; Farida Yuliaty (Dinasti Publisher, 2025)
The implementation of the Generic Open Source Hospital Management Information System (SIMGOSV2) is essential to support effective and efficient healthcare services. However, challenges such as limited infrastructure, user resistance, and staff competencies remain significant barriers. This study aims to analyze the factors influencing the successful implementation of SIMGOSV2 at Ryacudu District Hospital, Kotabumi, Lampung. A quantitative survey approach was employed, involving 124 purposively selected respondents from a population of 180 employees. Data were collected through questionnaires and analyzed using multiple linear regression to examine the effects of human resource competence, managerial commitment, external factors, and technology on the successful implementation of SIMGOSV2. Findings indicate that human resource competence and managerial commitment significantly affect SIMGOSV2 implementation, while external and technological factors show weaker effects. The coefficient of determination (R²) of 0.681 suggests that 68.1% of the variation in successful implementation is explained by the studied variables. The success of SIMGOSV2 implementation is strongly influenced by human and managerial aspects. Hospitals should strengthen training, motivation, and managerial support while evaluating system features to better enhance work productivity. This study confirms that technological factors are the strongest determinant of SIMGOSV2 implementation success in regional hospitals.